Peran Zakat Sebagai Pengurang Penghasilan Kena Pajak - Desi Handayani (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2022)
Zakat and taxes are two expenses that must be met by Muslim taxpayers. But there is a thought when zakat is paid whether the tax must still be paid. Does it not cause a double burden for Muslim taxpayers. This concern is accommodated by the government by making zakat as deduction from taxable income. With a decrease in taxable income will certainly reduce the tax burden that must be paid. But there are still many ordinary people who do not know this. For those who already know, there are still many who have not used it, because there are still many of the taxpayers pay their zakat not through an amil zakat institution or agency established or legalized by the government. So that the income zakat paid cannot reduce the taxable income. This study aims to describe in a narrative way how zakat can be a deduction from taxable income by referring to the applicable laws and regulations. Based on the description, income zakat can be deducted from taxable income if it meets the requirements set by the government in the laws and regulations and supporting regulations. It is hoped that this research can be a medium of socialization for the community to take advantage of zakat as a deduction from taxable income. For the government to make a policy of zakat as a tax deduction as in a country where the majority of the population is Muslim.